2016
DOI: 10.1136/emermed-2016-205950
|View full text |Cite
|
Sign up to set email alerts
|

Skin and soft tissue infection management failure in the emergency department observation unit: a systematic review

Abstract: A higher rate of EDOU management failure in SSTIs than the generally accepted rate of 15% was observed in most studies identified by this review. Risk factors identified were varied, but presence of a fever and elevated inflammatory markers were commonly associated with failure of EDOU admission by multiple studies. Recognition of risk factors and the increased application of clinical decision tools may help to improve disposition of patients at high risk for clinical deterioration or management failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…This finding is similar to those of studies performed in the Middle East and Asia (Chou et al, 2015;Al Jalaf et al, 2018) and in contrast to the findings of other studies in Europe and the USA (Lipsky et al, 2007;Macía-Rodríguez et al, 2017), where an increase in prescription of antibiotics active against MRSA (Szumowski et al, 2007;Hersh, 2008) was noted in emergency rooms in the last decades (Pallin et al, 2008). A systematic review by Abetz et al reported a frequency of treatment failure of 15-38% in SSTI, and an MRSA infection was implicated in this outcome (Abetz et al, 2018). Macía-Rodríguez et al reported that an inadequate empirical therapy of SSTI resulted in greater mortality (OR 44.74, 95% CI 5.40-370.73) (Macía-Rodríguez et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…This finding is similar to those of studies performed in the Middle East and Asia (Chou et al, 2015;Al Jalaf et al, 2018) and in contrast to the findings of other studies in Europe and the USA (Lipsky et al, 2007;Macía-Rodríguez et al, 2017), where an increase in prescription of antibiotics active against MRSA (Szumowski et al, 2007;Hersh, 2008) was noted in emergency rooms in the last decades (Pallin et al, 2008). A systematic review by Abetz et al reported a frequency of treatment failure of 15-38% in SSTI, and an MRSA infection was implicated in this outcome (Abetz et al, 2018). Macía-Rodríguez et al reported that an inadequate empirical therapy of SSTI resulted in greater mortality (OR 44.74, 95% CI 5.40-370.73) (Macía-Rodríguez et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Following admission to an ESSU for management of cellulitis, a high proportion (34.8%) of patients either had their care transferred to an inpatient team, or overstayed the ESSU time limit. This high rate of transfer of care or overstay is consistent with findings from a recent systematic review on the topic (15–38%) . In contrast to previously documented risk factors for these occurrences that include high initial temperature, elevated WBC and known methicillin‐resistant Staphylococcus aureus exposure or positive culture – derived primarily from studies on patient populations in the USA, this study found obesity, IVDU, elevated WBC and an elevated CRP were independently associated with transfer of care or overstay.…”
Section: Discussionsupporting
confidence: 89%
“…This high rate of transfer of care or overstay is consistent with findings from a recent systematic review on the topic (15–38%) . In contrast to previously documented risk factors for these occurrences that include high initial temperature, elevated WBC and known methicillin‐resistant Staphylococcus aureus exposure or positive culture – derived primarily from studies on patient populations in the USA, this study found obesity, IVDU, elevated WBC and an elevated CRP were independently associated with transfer of care or overstay. Knowledge of such risk factors can inform appropriate guidelines for ESSU admission and thereby improve patient flow and reduce length of stay in the ED and hospital.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations